Ultrasonic and seismic constraints on crystallographic preferred orientations of the Priestley Glacier shear margin, Antarctica - F. Lutz; D. J. Prior; H. Still; M. H. Bowman; B. Boucinhas; L. Craw; S. Fan; D. Kim; R. Mulvaney; R. E. Thomas; C. L. Hulbe (The Cryosphere, 2022)
Crystallographic preferred orientations (CPOs) are particularly important in controlling the mechanical properties of glacial shear margins. Logistical and safety considerations often make direct sampling of shear margins difficult, and geophysical measurements are commonly used to constrain the CPOs. We present here the first direct comparison of seismic and ultrasonic data with measured CPOs in a polar shear margin. The measured CPO from ice samples from a 58 m deep borehole in the left lateral shear margin of the Priestley Glacier, Antarctica, is dominated by horizontal c axes aligned sub-perpendicularly to flow. A vertical-seismic-profile experiment with hammer shots up to 50 m away from the borehole, in four different azimuthal directions, shows velocity anisotropy of both P waves and S waves. Matching P-wave data to the anisotropy corresponding to CPO models defined by horizontally aligned c axes gives two possible solutions for the c-axis azimuth, one of which matches the c-axis measurements. If both P-wave and S-wave data are used, there is one best fit for the azimuth and intensity of c-axis alignment that matches the measurements well. Azimuthal P-wave and S-wave ultrasonic data recorded in the laboratory on the ice core show clear anisotropy of P-wave and S-wave velocities in the horizontal plane that match that predicted from the CPO of the samples. With quality data, azimuthal increments of 30∘ or less will constrain well the orientation and intensity of c-axis alignment. Our experiments provide a good framework for planning seismic surveys aimed at constraining the anisotropy of shear margins.